The registration of ships and the South African ships register- current and proposed (and some related aspects) - Melunsky, David (Centre for Law and Society, 2026)
As part-of the Department of Transport's review of maritime transport, a preliminary draft Registration of Ships Bill and Registration of Ships Regulations has been prepared and Circulated for comment. The preliminary draft bill (referred to herein as the draft bill"' its regulations are sometimes referred to separately herein as "the draft regulations") is primarily an attempt to "amend and restate the law relating to the registration of ship" .1 Perhaps more accurately, the draft bill is the beginning of a process for the much needed "update" of the current registration regime. This is at present governed by the Merchant Shipping Act, No. 57 of 1951, which is to great measure based upon_ the legislation and policies of the nineteenth century. Developments in the shipping industry (for example, the practice of" flagging-out" ships and the specific practice of re-flagging demise-chartered ships); advances in communication (making possible the creation of a central ships register instead of having registers in the various ports); and a changing political, economic and social climate (the birth of many countries, the increasing number of registers on offer to shipowners, the globalisation of trade, South Africa's new standing in the world, the move away from strict nationalistic shipping policies), have all created the need for a new registration regime.